Variation in care for children undergoing the Fontan operation for hypoplastic left heart syndrome - Eckhauser, Aaron W. (Cardiol Young, 2019)
BACKGROUND: The Single Ventricle Reconstruction Trial randomised neonates with hypoplastic left heart syndrome to a shunt strategy but otherwise retained standard of care. We aimed to describe centre-level practice variation at Fontan completion. METHODS: Centre-level data are reported as median or median frequency across all centres and range of medians or frequencies across centres. Classification and regression tree analysis assessed the association of centre-level factors with length of stay and percentage of patients with prolonged pleural effusion (>7 days). RESULTS: The median Fontan age (14 centres, 320 patients) was 3.1 years (range from 1.7 to 3.9), and the weight-for-age z-score was −0.56 (−1.35 = 0.44). Extra-cardiac Fontans were performed in 79% (4–100%) of patients at the 13 centres performing this procedure; lateral tunnels were performed in 32% (3–100%) at the 11 centres performing it. Deep hypothermic circulatory arrest (nine centres) ranged from 6 to 100%. Major complications occurred in 17% (7–33%). The length of stay was 9.5 days (9–12); 15% (6–33%) had prolonged pleural effusion. Centres with fewer patients (<6%) with prolonged pleural effusion and fewer (<41%) complications had a shorter length of stay (<10 days; sensitivity 1.0; specificity 0.71; area under the curve 0.96). Avoiding deep hypothermic circulatory arrest and higher weight-for-age z-score were associated with a lower percentage of patients with prolonged effusions (<9.5%; sensitivity 1.0; specificity = 0.86; area under the curve 0.98). CONCLUSIONS: Fontan perioperative practices varied widely among study centres. Strategies to decrease the duration of pleural effusion and minimise complications may decrease the length of stay. Further research regarding deep hypothermic circulatory arrest is needed to understand its association with prolonged pleural effusion.